In Need of an Extended Research Approach: The Case of the ‘Neglected African Diaspora’ of the Post-Communist Space - Tarrósy, István (Pécs journal of international and European law, 2019)
This paper seeks to extend the academic discussion and research of the global African diaspora by drawing attention to Africans living in post-Communist spaces. So far, both literature and for- eign policies of countries of the former Eastern Bloc hardly ever made mention of this ‘neglected diaspora’. First, the paper underscores the relevance of specific research connected with African communities across Central and Eastern Europe, as well as present-day Russia. Second, it intro- duces the history, motivations, background and contemporary situation of the marginal but grow- ing African population in Hungary. It will show how finally the Hungarian government implements a pragmatic foreign policy (partly) on Africa and African development co-operation. In this effort, it considers Africans who either had obtained a university degree before 1989 at a Hungarian uni- versity, or came to the country during the democratic rule, as true bridges: they can foster newly defined relations. The place, role and potentials of these African migrants in the unique Hungar- ian migration environment will also be discussed. Increased illegal migration flows towards the European Union via the Serbian–Hungarian border region of the Schengen Zone in the first half of 2015 and the policies the Hungarian government introduced in the wake of this unprecedented push makes the discussion even more topical, in particular, as of early April 2019, a government “Africa Strategy” was also published.